Effect of atorvastatin on haemostasis, fibrinolysis and inflammation in normocholesterolaemic patients with coronary artery disease - Walter, Thomas; Szabo, Sebastian; Süselbeck, Tim; Borggrefe, Martin; Lang, Siegfried; Swoboda, Stefanie; Hoffmeister, Hans Martin; Dempfle, Carl-Erik (Clinical drug investigation, 2010)
Treatment with HMG-CoA reductase inhibitors (statins) reduces the morbidity and mortality of coronary artery disease (CAD). In addition to their lipid-lowering actions, pleiotropic effects of statins have been demonstrated. The aim of the present study was to assess if atorvastatin therapy has an impact on haemostasis, fibrinolysis and inflammation in normocholesterolaemic patients with CAD.
Online veröffentlicht am 24. August 2012
Gesehen am 04.10.2023